Innovation, Dynamics of Competition and Market Dynamics - Gottinger, Hans W. (Archives of Business Research, 2016)
Largely from the perspective of network economics we look into a specific range of economic studies on competition, innovation and technological change with a view to relating theories, models and ideas on how best to analyze the impact of innovation and market dynamics on scale and scope of network industries. Innovation has a major network inducing effect, so has competition. Competition in this context always carries dynamic features and is intrinsically linked to games of strategy . Our review focuses on both the interaction of competition and innovation and discusses prevailing models of innovation and studies that fall within other traditions such as Schumpeterian economics.